JAMAAH AHMADIYAH (Kesesatan yang Merusakan Kerukunan Umat Seagama) - Akbarizan Akbarizan (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2009)
Some people consider Ahmadiyya" is one of a group or school of the Muslim group, brcause Ahmadiyya differ only in matters of furu' Indeed Ahmadflya has nothing to do with Islam. Ahmadiyyah has deceived the human race and sell the name of Islam. After studying and reviewing his teachings, misleading and damaging Ahmadiyya community harmony religion (the Muslims) and outside the Ahmadiyya Muslim.